Application of Gamification-Based Multisensory Methods in Improving the Brain Ability of Children with Intellectual Disabilities in Learning English Vocabulary - Rahmatullah, Ilham (East Asian Journal of Multidisciplinary Research, 2024)
This study addresses the challenges of English vocabulary acquisition for children with intellectual disabilities in Indonesia, focusing on North and West Lombok. A gamification-based multisensory approach was tested with 60 students using a mixed-methods approach. The results showed significant vocabulary improvement, with post-test scores markedly higher than pre-test scores. The study highlights the method's potential to enhance cognitive engagement and motivation, offering a scalable, culturally appropriate intervention for special education in Indonesia. These findings provide actionable insights for educators and policymakers aiming to advance educational equality and inclusion for children with disabilities.